Relationship between psychological adaptability and work engagement of college teachers within smart teaching environments: the mediating role of digital information literacy self-efficacy - Fan, Shiyi; Yu, Zeyuan; Zheng, Xin; Gao, Chunhai (Frontiers in Psychology, 2023)
Introduction Integrating the Internet and traditional teaching has enriched teaching resources and methods and introduced many advanced digital media. The smart teaching process is influenced by teachers' psychological adaptability, which can be affected by teachers' work engagement. However, the relationship between the two has not received sufficient attention in the literature. This study aims to analyze the relationship between college teachers' psychological adaptability and work engagement in a smart teaching environment. Methods Applying structural equation modeling (SEM) to a sample of 373 front-line teachers, this study focuses on the mediating effect of digital information literacy self-efficacy on the relationship between teachers' psychological adaptability and work engagement. Results The results show that the four dimensions of college teachers' psychological adaptability strongly influence work engagement and digital information literacy self-efficacy. In particular, teachers' psychological adaptability and work engagement are positively correlated; teachers' self-efficacy can positively affect the three dimensions of their work engagement, and teachers' psychological adaptability can positively affect their digital information literacy self-efficacy. Conclusion The above results can serve as a basis for the development and improvement of the training of college teachers and the implementation of smart teaching. The study findings highlight the importance of training teachers on information technology teaching and implementing measures to enhance teachers' digital information literacy self-efficacy. Training should focus on the knowledge and skills of teachers using information technology teaching and increase the practical links of teachers using information technology teaching.